PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP KREATIVITAS SISWA DALAM PEMBELAJARAN MATEMATIKA - ismi zakiah; Hadi Kusmanto (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2017)
This research is motivated by the lack of students creativity in mathematics. It is influenced by the learning model used. Learning model that can help students understand about the material one of them is cooperative learning model type make a match. The purpose of the research is to assess influence of cooperative learning type make a match towards of students creativity. This research use a experimental method, with the research population is 55 students of class VII. The sample is VII-B class with 28 students. The research instrument that used are test and the scale. The result of the research shows; the students response to learning by using cooperative learning model type make a match got a good category with an average 74,8%; students creativity in experimental class categorized good with average score 70,54; there are the sicnifikance influence between cooperative learing model type make a match toward students vreativities in matematic is 51,8%.Keywords : Make A Match, Student Creativity